Canon Twice Re/canonized: Teaching Shakespeare in Croatia Today - Ciglar-Žanić, Janja (1996)
To interpret the meanings of an established literary canon of another culture has never been a particularly simple task. Even within the literary study - paradigm, with its authorialism, its notions of textual unity and the eternalisation of value, the task had been one of formidable complexity and great challenge. It has always required a comparatively structured awareness of the processes involved in the translation/transculturation of historical texts. A necessity to recognize the culture-specific features of reader-response to the texts from other cultures continually presents an aditional level of complexity, especially in cases of texts - such as Shakespeare's - with status of the cultural symbol.
The cultural studies paradigm with its nullification of some central oppositions (notably between "high" and "popular" culture) and its problematising the questions of value has not diminished the complexities involved in reading such texts. Nor its challenges. How does one uphold a notion about the fixity of some among the canonical text's meanings while at the same time emphasizing an active transformation of textual meanings in different historical and cultural contexts?
The paper proposes to discuss both the difficulties and the challenges involved in the task, as they are encountered in teaching Shakespeare at the university degree level in Croatia today.
Projekt MZOS
ENG